Revisão do diagnóstico de enfermagem estilo de vida sedentário : análise de conceito e validação por especialistas - Guedes, Nirla Gomes (2011)
The objective of this study is to validate the nursing diagnosis of sedentary lifestyle (SL) in individuals with hypertension, based on the idea that it is necessary to evaluate this diagnosis in relation to the appropriateness of the definition, the defining characteristics (CD) and the related factors (FR) in this population and that there are other clinical indicators relevant to the SL, in addition to the factors defined by NANDA-I. The validation of the SL was conducted in two stages: concept analysis and validation by expert. To implement the first stage we used the integrative literature review of five databases (LILACS, CINAHL, PubMed, Scopus and Cochrane), with the following combinations of descriptors and equivalent in English and Spanish: Sedentary lifestyle & Hypertension and Physical inactivity & Hypertension. After application of the inclusion and exclusion criteria, the remaining 43 studies which supported the analysis of the concept. After this stage, an instrument was built containing the FR and identified CD, with their respective conceptual definitions and empirical references. This instrument was subjected to the evaluation of 48 specialist nurses in terminologies of nursing and/or sedentary lifestyle and/or hypertension. The validation process has led to the following results: change of the definition of the SL, definition of some clinical indicators and the addition of others. In this way, it is recommended the following definition to the SL: It refers to a life style in which the individual does not perform physical exercise in frequency, duration nor the recommended intensity. The final proposal of the validation process incorporates eleven FR,: " defective knowledge on the benefits that the physical activity brings to the health and / or on the consequences of the sedentary life style ”; “ lack of motivation for practicing physical exercise ”; “ lack of interest in exercising ”; “ lack of resources (time, money, place, security and equipment) ”; “ lack of training to perform physical exercise ”; “ attitudes, beliefs and habits of health that make difficult the practice of physical activity ”; “ lack of social support for the practice of physical exercise ”; “ lack of confidence for practice of physical exercise ”; “ damaged mobility ”; “ intolerance to the activity ”; “ report of pain ”. The first five described FR are those who already compose the taxonomy II of the NANDA-I, being the fifth one the only one with the same nomination. Regarding the CD, it is recommended: the separation of the present characteristic in the NANDA-I “ demonstrates lack of physical conditioning ” in “reduced cardio-respiratory capacity ”, “ reduced muscular strength ” and “reduced flexibility of the articulations”; the maintenance of “ chooses routines without physical exercises ” and “ it verbalizes preference for activities with little physical exercise ”; and the addition of "excess weight"; “ low performance in the instrumental activities of daily life ” and “ it does not carry out physical activities in the leisure time”. As the conceptual definitions and empirical references built, were, in general, evidenced statistically proportions of matching within the specialists not less than 80% (p > 0.05) and values index of content validity of diagnosis more than 0.70 . The same was found for the 11 FR, and for the eight CD. It is considered that validation process assumed a direction for the diagnostic accuracy of clinical indicators of SL, contributing with the refinement and improvement of this diagnosis, and of its components. It is essential that the Nursing to appropriate this diagnosis in different contexts and that nurses use their technologies with a view to enhance and amplify the knowledge and the autonomy of the profession itself.